130k views
0 votes
Please answer this question with steps

Please answer this question with steps-example-1
User Kqnr
by
4.5k points

2 Answers

3 votes

Answer:

see explanation

Explanation:


(1)/(3) a³ -
(3)/(4) a² -
(5)/(2) - (
(5)/(2) a² +
(3)/(2) a³ +
(a)/(3) -
(6)/(5) ) ← distribute parenthesis by - 1

=
(1)/(3) a³ -
(3)/(4) a² -
(5)/(2) -
(5)/(2) a² -
(3)/(2) a³ -
(a)/(3) +
(6)/(5) ← collect like terms

= (
(1)/(3) a³ -
(3)/(2) a³ ) + (-
(3)/(4) a² -
(5)/(2) a² ) -
(a)/(3) + (-
(5)/(2) +
(6)/(5) ) ← change to common denominators

= (
(2)/(6) a³ -
(9)/(6) a³ ) + (-
(3)/(4) a² -
(10)/(4) a² ) -
(a)/(3) + (-
(25)/(10) +
(12)/(10) ) ← simplify

= -
(7)/(6) a³ -
(13)/(4) a² -
(1)/(3) a -
(13)/(10)

User Surt
by
4.9k points
7 votes

Answer:

Explanation:


\sf (1)/(3)a^3-(3)/(4)a^2-(5)/(2)-\left[(5)/(2)a^2+(3)/(2)a^3+(a)/(3)-(6)/(5)\right]=


\sf = (1)/(3)a^3-(3)/(4)a^2-(5)/(2)-(5)/(2)a^2-(3)/(2)a^3-(a)/(3)+(6)/(5)\\\\\\( Combine \ like \ terms)\\\\= (1)/(3)a^3 -(3)/(2)a^3 -(3)/(4)a^2-(5)/(2)a^2-(a)/(3)-(5)/(2)+(6)/(5)\\\\=\left[(1*2)/(3*2)-(3*3)/(2*3)\right]a^3 + \left[-(3)/(4)-(5*2)/(2*2)\right]a^2-(a)/(3)+\left[-(5*5)/(2*5)+(6*2)/(5*2)\right]\\\\\\


\sf ==\left[(2)/(6)-(9)/(6)\right]a^3+\left[-(3)/(4)-(10)/(4)\right]a^2-(a)/(3)+\left[-(25)/(10)+(12)/(10)\right]\\\\=(2-9)/(6)a^3+((-3-10))/(4)a^2-(a)/(3)+((-25+12))/(15)\\\\


\sf = (-7)/(6)a^3+ ((-13))/(4)a^2-(a)/(3)+((-13))/(15)\\\\=-(7)/(6)a^3-(13)/(4)a^2-(a)/(3)-(13)/(15)

User Makesha
by
5.0k points